2016
DOI: 10.5301/uro.5000193
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C: New Strategies to Improve Efficacy of a Well-Known Therapy

Abstract: Mitomycin C (MMC) as an intravesical chemotherapeutic agent is a well-known option for treatment of nonmuscle invasive bladder cancer (NMIBC) recurrence; it is probably the most commonly used agent given its low rate of side effects and its efficacy.Both the American Urologic Association (AUA) and European Association of Urology (EAU) consider MMC as a standard treatment for immediate single-dose postoperative treatment and for adjuvant therapy in low and intermediate-risk NMIBC.Despite the popularity of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The optimal dose and course of treatment when MMC is used as an adjuvant infusion therapy remain controversial. The 3-5 year recurrence rate in patients treated with MMC is only 8% lower than that of patients treated with TURBT [8]. Therefore, it is particularly urgent and important to improve the perfusion efficiency of MMC.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The optimal dose and course of treatment when MMC is used as an adjuvant infusion therapy remain controversial. The 3-5 year recurrence rate in patients treated with MMC is only 8% lower than that of patients treated with TURBT [8]. Therefore, it is particularly urgent and important to improve the perfusion efficiency of MMC.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, multiple repeated transurethral resections, intravesical chemotherapy, or intravesical immunotherapy are often needed after the initial surgery [7]. For patients with NMIBC who are at a high risk of recurrence, mitomycin C (MMC) or Basile Calmette-Guerin (BCG) perfusion therapy is the main form of treatment [8]. However, there is a shortage of available BCG products [9].…”
Section: Introductionmentioning
confidence: 99%
“…Its cytotoxic effect results from DNA cross-linking, which inhibits DNA synthesis and cell proliferation. 16 While MMC is a well-established treatment for low-risk NMIBC, 17 its effectiveness in high-risk patients remains a point of contention, thereby necessitating further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Mitomycin C, a chemotherapeutic agent, interacted with MX1. It is used to treat many cancer types [218][219][220][221]. A systems biological study revealed that mitomycin C interacted with MX1, a key protein in an IPIN, suggesting further studies in the role of the drug in antiviral stimulation [50].…”
Section: Potential Drugs To Cure Severe Covid-19 Patientsmentioning
confidence: 99%